2019
DOI: 10.1002/ps.5306
|View full text |Cite
|
Sign up to set email alerts
|

Rain‐based soil solarization for reducing the persistent seed banks of invasive plants in natural ecosystems – Acacia saligna as a model

Abstract: BACKGROUND: A large persistent seed bank of invasive plants is a significant obstacle to restoration programs. Soil solarization was demonstrated to be an effective method for reducing the seed bank of Australian acacias. However, use of this method in natural habitats might be limited due to the requirement to moisten the soil by irrigation. This study examined the possibility of replacing irrigation by trapping the soil moisture caused by the most recent rainfall, i.e. rain-based soil solarization (RBS). RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Using transparent polyethylene sheets, the temperature of the soil at a depth of 0-20 cm usually reaches 40-60 °C, leading to the eradication of pathogens, arthropod pests, and weeds. This soil treatment has been already tested to manage invasive seed banks and lead to significantly reduced viability of buried Acacia seeds, including the invasive species A. saligna, A. murrayana and A. sclerosperma, by exposing seeds to lethal hydrothermal conditions, constituting an effective method to reduce the persistent invasive seed bank of those species [54][55][56]. Considering the C. edulis seeds' thermic sensitivity described here and the fact that a 77.6% of this species' soil seed bank is mainly found in the species' litter and the first 0-5 soil cm [30], soil solarization may constitute a promising tool for invaded soil seed bank eradication.…”
Section: Artificial Aging To Assess Invasive Potentialmentioning
confidence: 99%
“…Using transparent polyethylene sheets, the temperature of the soil at a depth of 0-20 cm usually reaches 40-60 °C, leading to the eradication of pathogens, arthropod pests, and weeds. This soil treatment has been already tested to manage invasive seed banks and lead to significantly reduced viability of buried Acacia seeds, including the invasive species A. saligna, A. murrayana and A. sclerosperma, by exposing seeds to lethal hydrothermal conditions, constituting an effective method to reduce the persistent invasive seed bank of those species [54][55][56]. Considering the C. edulis seeds' thermic sensitivity described here and the fact that a 77.6% of this species' soil seed bank is mainly found in the species' litter and the first 0-5 soil cm [30], soil solarization may constitute a promising tool for invaded soil seed bank eradication.…”
Section: Artificial Aging To Assess Invasive Potentialmentioning
confidence: 99%
“…weeks after the onset of the solarization treatment, the non-dormant fraction was higher in the solarization treatment than in the control. As suggested in our previous studies (Cohen et al 2008(Cohen et al , 2018(Cohen et al , 2019, we assume that the release from dormancy is probably the critical stage leading to the deterioration of the seed bank through a weakening effect occurring during soil solarization.…”
Section: The Underlying Mechanism Of Seed Bank Reductionmentioning
confidence: 54%
“…Therefore, in dry habitats, the regular soil solarization method, which includes pre-irrigation, is recommended. Alternatively, satisfactory results can also be achieved by covering the soil with transparent polyethylene following the last rains (RBS method, Cohen et al 2019). In wetlands, covering the soil during the summer without pre-irrigation (i.e., dry solarization, as used in this study) has also been found to be effective.…”
Section: Application and Implicationsmentioning
confidence: 89%
See 2 more Smart Citations